In-situ characterization of Jatigede local Roid banana (Musa spp.) based on morphological and agronomical characteristics - Ismail, Ade; Pratiwi, Vika Faraditha; Maulana, Haris; Bari, Ichsan Nurul; Maharani, Yani; Kusumah, Fajar Maulana Wijaya (Universitas Padjadjaran, 2023)
Banana (Musa spp.) is one of the agricultural commodities that’s widely cultivated and used by the local community. Currently, only 101 types of local varieties of bananas are registered in Indonesia; one of them is the Roid banana from Jatigede District. Roid bananas grow wild without any mandatory special care. Continuous use without any conservation and preservation efforts can lead to scarcity of Roid banana germplasm as a genetic resource. Therefore, it is necessary to identify the distribution and diversity of Roid bananas through in situ exploration and characterization activities. This study aimed to identify the potential for genetic diversity and develop conservation efforts for the local variety of Roid banana (Musa spp.) in Jatigede District. This research was conducted from November 2021 - March 2022 in three villages in Jatigede District: Ciranggem Village, Jemah Village, and Mekarasih Village. The research used exploratory, survey, and interview methods as data collection techniques. Based on the results of the study, Jatigede District has a wide genetic diversity and distant kinship among Roid banana accessions. Characters that contributed to genetic diversity among accessions were the width of the midrib margin, the diameter of the bunch, and the length of the pseudostem. MS1.3 was the selected accession with its potential characteristics: more combs in bunches, leaf width of 71-80 cm, leaf length of 171-220 cm, and the number of rhizomes > 5 tillers.